Analysis Of Financial Report Presentation Based On Emkm Sak (Case Study Of Akas Travel In Sukamerindu, Bengkulu City) - Juanida, Erika; Soleh, Ahmad; Hidayah, Nenden Restu (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2025)
SAK EMKM is prepared to meet the financial reporting needs of micro, small, and medium entities. Law No. 20 of 2008 regarding Micro, Small, and Medium Enterprises can be used as a reference in defining and providing a quantitative range for EMKM. Accurate and transparentfinancial statement presentation is key to business success, especially for micro, small, and medium entities (UMKM). In this context, the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) are crucial. Financial reports provide information that describes the financial condition of a company, and this information can further illustrate the company's performance. Based on this description, running a business requires financial recording to see how far the business has developed. SAK EMKM is a simplified standard because it regulates general transactions conducted by EMKM, and its measurement basis purely uses historical costs, allowing EMKM to record their assets an liabilities at their acquisition costs. Travel Akas still records financial statements simply, only noting cash inflows and outflows. Given the owner's lack of understanding of SAK EMKM, some aspects still do not comply with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). The type of research used is qualitative research. It is conducted in-depth through data collection. The research method is based on positivism, aiming to analyze and measure compliance or implementation of accounting standards based on numerical and statistical data. The research approach used is descriptive. This descriptive method analyzes and classifies: investigates, using documentation techniques, interviews, and observations, conducted at Travel Akas in Sukamerindu, Bengkulu City by analyzing, differentiating, selecting items for use, and regrouping them according to specific criteriaand seeking relationships to interpret their meanings. Financial statement presentation refers to the process of preparing and presenting accounting documents, including the balance sheet, income statement, and cash flow statement. The Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) are accounting guidelines established by the Indonesian Institute of Accountants to assist UMKM in preparing simple, transparent financial statements that comply with applicable accounting principles. The Travel Akas business operates in the tourism sector. The owner of this business is Mr. Ahmad Afsi, located in Sukamerindu, Bengkulu City. The Travel Akas business is classified as a service business as it provides transportation, accommodation, and travel experiences. The research findings indicate that the financial statements prepared by the Travel Akas business in Sukamerindu, Bengkulu City have included cash statements, income statements, and balance sheets. The financial information contains records of the company, both transaction records and cash, and financial statements processed over a specified period. The objective is to provide information regarding the financial position and performance to understand the health of the business's finances.